160 Studies of Sperm DNA Methylation Variations and Their Potential Regulations on Production and Reproduction Traits in Cattle and Pigs. (8th October 2021) - Yu, Ying; Chen, Siqian; Liu, Shuli; Fang, Lingzhao; Zhang, Shengli
Abstract: Identification of inter-individual variations of sperm DNA methylation is very essential for elucidating phenotypic variation of reproduction and production traits. We had generated 28 sperm whole genome sequencing (WGBS) data from healthy individuals. We detected 46 variably methylated regions (VMRs) significantly (P < 5.77 × 10 −5 ) associated with reproduction traits. These significant VMRs were also co-localized (±10 kb) with genes related to sperm motility and reproduction, including ZFP36L1, CRISP2 and HGF. To further identify epigenomic markers associated with reproduction and production traits, we generated WGBS dada for a specific pair of monozygotic twin artificial insemination Holstein bulls with moderately different sperm qualities (Bull1 > Bull2). We found 528 differentially methylated regions between the twin bulls, which spanned or overlapped with 309 differentially methylated genes (DMG). These DMG were particularly associated with reproduction, embryo development and the nervous system. To further obtain DNA methylation markers involved in the diversity of porcine reproduction and production traits due to long-term artificial selection, we profiled sperm DNA methylation of three commercial pig breeds–Duroc, Landrace and Large White. we found the hypomethylated regions (HMRs) were highly conserved among pig breeds, while 1040–1666 breed-specific HMRs were identified and associated with the QTLs of embryonic developmental and phenotypic changes. By integrating reduced representation bisulfite sequencing public data of pig testis, we further defined 1743 conservative HMRs between sperm and testis, which may play a role in spermatogenesis process. Overall, our studies demonstrated associations of sperm DNA methylation with bovine and porcine production and reproduction traits, highlighting the potential of epigenomic information in genomic improvement programs for livestock. (*: yuying@cau.edu.cn)